Differential organ responses to fumonisins in rabbits: kidney, liver, and spleen membrane fatty acid composition, oxidation markers, and histopathology - Ali, Omeralfaroug; Agyarko, Edward; Gerencsér, Zsolt; Balogh, Krisztián; Mézes, Miklós; Kovács, Melinda; Maki, Mohamed; Besselma, Noureddine; Yakubu, Haruna Gado; Szabó, András (Frontiers in Veterinary Science, 2025)
The study assessed the kidney, liver, and spleen of adult male rabbits (n = 10/group) in relation to fumonisin B series exposure (10 and 20 mg FB1 + FB2 + FB3/kg feed) over a period of 65 days. The rabbit growth and feed intake remained unaffected; meanwhile, kidney and liver weights increased. The highest dose provided greater alterations in total phospholipid fatty acid profiles, particularly in the kidney (C20:5n3 and C18:0) and spleen (C18:1n7, C22:0, C20:4n6, and C20:5n3) than in the liver. Neither the kidneys nor the spleens demonstrated modifications in their antioxidant (glutathione and glutathione peroxidase) and lipid peroxidation (malondialdehyde) markers; however, there was a marked drop in the liver glutathione concentration and glutathione peroxidase of the group that administered 20 mg FBs/kg diet, while liver malondialdehyde levels remained unchanged. Serum clinical measures revealed elevated creatinine, total cholesterol, high-density lipoproteins, and gamma-glutamyl transferase activity at the highest FBs dose. Histological scores revealed mild nephrotoxicity and hepatotoxicity in the 20 mg FBs/kg group, accompanied by a mild to moderate lesion score in the spleen. Overall, FBs exposure elicited diverse organ-specific adverse effects, with severity increasing at higher doses. Despite these alterations, rabbits demonstrated adaptability to FBs over the study period, as indicated by steady growth performance.